POLITICS OR PIETY? UNDERSTANDING PUBLIC PIETY AND POLITICAL EXPRESSIONS OF INDONESIAN MUSLIM IN ONLINE SPHERE - Salma, Aqida Nuril (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
In today’s digital age, one of the most significant shifts in the field of Islam in Indonesia is the increasing reliance of Muslims on social media when practicing and expressing their faith and religiosity. The expressions generally reflected in the consumer behavior and everyday lives of Indonesian Muslims, with their preference for Islamic banking, Islamic schools, Islamic fashion, Islamic medicines and most importantly, today Indonesian Muslims like to present these practices on their social media accounts. However, public expressions of piety have been apparent in the political life of Indonesian Muslims as Indonesia’s political landscape has undergone significant changes after the controversy surrounding Jakarta Gubernatorial Election. Although religion has often been ignored as an important political factor, but it can’t be denied that both are actually the biggest public parts of many people’s lives. Therefore, this paper argues that political contexts are critical aspects of modern formations of piety. Based on online observations combined with computational method, this paper tries to analyzes intriguing examples of how social media, the religious, and the everyday politics intersect, focusing on contemporary expressions of piety through political attitudes in an online sphere.